The Iliad - Homer (Ecco, 2015)
"Composed around 730 B.C., Homer's Iliad recounts the events of a few momentous weeks in the protracted ten-year war between the invading Achaeans, or Greeks, and the Trojans in their besieged city of Ilion. From the explosive confrontation between Achilles, the greatest warrior at Troy, and Agamemnon, the inept leader of the Greeks, through to its tragic conclusion, The Iliad explores the abiding, blighting facts of war. Carved close to the original Greek, acclaimed classicist Caroline Alexander's new translation is swift and lean, with the driving cadence of its source--a translation epic in scale and yet devastating in its precision and power." --